Synthesis, characterisation and corrosion inhibition screening: Cu[EtBenzdtc]2 and Cu[BuMedtc]2 / Nur Alia Atiqah Alias ... [et al.] - Alias, Nur Alia Atiqah; Zolkifli, Nabilah Syakirah; Mohd Radzi, Mimi Wahidah; Dzulkifli, Nur Nadia (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Mild steel plays an essential part in many construction industries due to its low cost and excellent mechanical properties. However, the use of strong acid in pickling, construction, and oil refining processes adds to a serious corrosion problem for mild steel. Two Cu(II) dithiocarbamate (DTC) complexes were successfully synthesised, namely Cu(II) ethyl-benzyl DTC (Cu[EtBenzdtc]2) and Cu(II) butyl-methyl DTC (Cu[BuMedtc]2) complexes, by a condensation reaction and subsequently used to scrutinise the corrosion resistance activity towards mild steel in acidic media. The proposed structures of complexes were characterised by using the Fourier transform infrared (FTIR) and ultraviolet-visible (UV-Vis) spectroscopies. The melting point for Cu[EtBenzdtc]2 was found around 362–375°C, and 389–392°C for Cu[BuMedtc]2. The percentages of Cu(II) found in Cu[EtBenzdtc]2 and Cu[BuMedtc]2 were 7.6% and 7.5%, respectively. Both complexes were non-electrolyte based on the molar conductivity analysis. Their corrosion inhibition performances were tested by using a weight loss measurement. Cu[BuMedtc]2 showed a good result as a corrosion inhibitor compared to Cu[EtBenzdtc]2. The complexes showed good effectiveness in sulfuric acid (H2SO4) compared to hydrochloric acid (HCl) solution. Furthermore, Cu[BuMedtc]2 showed a good result as a corrosion inhibitor compared to Cu[EtBenzdtc]2 with the highest percentage of corrosion inhibition recorded at 91.8%. Meanwhile, the highest percentage of corrosion inhibition shown by Cu[EtBenzdtc]2 was only 86.9%. The lowest corrosion rate shown for Cu[BuMedtc]2 was 8.1944×10-4 cm-1 h-1. Meanwhile, the Cu[EtBenzdtc]2 showed the lowest corrosion rate only at 1.3194×10-3 cm-1 h-1. This implies that Cu[BuMedtc]2 showed lower corrosion rate but higher inhibition efficiency compared to Cu[EtBenzdtc]2.